Rancang Bangun Alat Pencetak Rempeyek Bulat Diameter 90mm - Hilda Porawati; Ahmad Imam Rifa’i; Gentur Pressa Reforandika; Fahrur Razi Ramadhan (Jurnal INOVATOR, 2022)
The peanut brittle product is very popular with the public so that many processors produce it, which are sold in various places, ranging from traditional markets to modern markets. The application of appropriate technology to increase production capacity is very much needed by Micro, Small and Medium Enterprises (MSMEs). In this research, the design of the peanut brittle fryer has been made using a round mold which has 10 peanut brittle molds with a spring lever system that is operated manually. The results showed that the frying pan had a diameter of 90 mm and a mold thickness of 2 mm and totaled 10 pieces in one frying process. The use of stainless material in the mold causes the dough to stick at the peanut frying stage.